2019
DOI: 10.1007/s12079-019-00527-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of PAR-1 mediated kinase receptor transactivation: Smad linker region phosphorylation

Abstract: Protease activated receptors (PARs) transactivate both epidermal growth factor receptors (EGFR) and transforming growth factor (TGF)-β receptors (TGFBR1) in vascular smooth muscle leading to the increased expression of genes (CHST11 and CHSY1) which are rate limiting for the enzymes that mediate hyperelongation of glycosaminoglycan (GAG) chains on the lipid-binding proteoglycan, biglycan. This is an excellent model to investigate mechanisms of transactivation as the processes are biochemically distinct. EGFR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 51 publications
2
29
0
2
Order By: Relevance
“…The engagement of receptor transactivation markedly expands the range of cellular responses attributable to the index cell surface, usually transmembrane, receptor. The current attributes of transactivation-dependent signalling encompass GPCR transactivation of kinase receptors [25,49,[59][60][61]. Mechanistic studies of GPCR transactivation-dependent signalling define a concrete signalling pathway [23,24,32,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The engagement of receptor transactivation markedly expands the range of cellular responses attributable to the index cell surface, usually transmembrane, receptor. The current attributes of transactivation-dependent signalling encompass GPCR transactivation of kinase receptors [25,49,[59][60][61]. Mechanistic studies of GPCR transactivation-dependent signalling define a concrete signalling pathway [23,24,32,49].…”
Section: Discussionmentioning
confidence: 99%
“…The current attributes of transactivation-dependent signalling encompass GPCR transactivation of kinase receptors [25,49,[59][60][61]. Mechanistic studies of GPCR transactivation-dependent signalling define a concrete signalling pathway [23,24,32,49]. LPS stimulates direct TGFBR1 intermediate phospho-Smad2 carboxy terminal via PI3K/ Akt and MAPK-dependent pathways in HSC-T6 hepatic stellate cells [43].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of C-terminal phosphorylation is very important for blocking the consequent Smad4 binding and extracellular matrix proteins transcription in the nucleus [48]. The linker region phosphorylation of Smad protein can be regulated by several kinases, such as PI3K/mTORC2, ERK, and JNK [48][49][50][51][52]. In Figure 2, we showed that 4-MSP can decrease the PDGF-BB-induced MEK/ERK, JNK, Akt, and p70S6K phosphorylation.…”
Section: Discussionmentioning
confidence: 89%
“…We observed a highly specific signalling pathway that regulates GAG chain elongation [ 50 ]. Growth factors, hormones and endotoxins acting via completely different receptor pathways signal specifically via the linker region of Smad2 transcription factor to regulate the genes associated with GAG chain modification [ 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. Furthermore, animal studies provide proof of principle that treating atherosclerosis-prone mice fed a high-fat diet an inhibitor of GAG elongation can prevent at least 50 percent of the lipid deposition [ 46 , 59 ].…”
Section: Endothelial Dysfunction and Mechanisms Of Atherosclerosismentioning
confidence: 99%